The effects of the visual presentation of an Influencer's Extroversion on perceived credibility and purchase intentions—moderated by personality matching with the audience. (March 2021) - Argyris, Young Anna; Muqaddam, Aziz; Miller, Steven
Abstract: Influencers are ordinary individuals who have amassed large followings by demonstrating expertise in various niches on social media sites. We aim to propose (1) the visual presentation of an Influencer's extroversion as an antecedent to source credibility and purchase intentions and (2) personality matching in terms of extroversion between an Influencer and their audience as a moderator of such relationships. We chose the source credibility model and the similarity-attraction model as our theoretical frameworks. In our controlled online experiment (n = 165), the profile of a brand ambassador of a fashion brand was curated to create two levels of extroversion (i.e. low vs. high extroversion). Participants' self-reported extroversion levels were counterbalanced in these two conditions to create a personality match with the Influencer, entitled "extroversion congruence." Our results suggest that the visual presentation of an Influencer's extroversion increases the perceived credibility of the Influencer and subsequent purchase intentions. Additionally, our findings show that these relationships were asymmetrically moderated by extroversion congruence: the positive effects of extroversion increase in the case of high extroversion among both the Influencer and their audience but decrease in the case of low extroversion.